2001
DOI: 10.1590/s0037-86822001000200010
|View full text |Cite
|
Sign up to set email alerts
|

AIDS e infecção pelo HIV no Brasil: uma epidemia multifacetada

Abstract: The HIV/AIDS epidemic is a dynamic unstable global phenomenon, constituting a veritable mosaic of regional sub-epidemics. As a consequence of the deep inequalities that exist in Brazilian society, the spread of HIV infection has revealed an epidemic of multiple dimensions undergoing extensive epidemiological transformations. Initially restricted to large urban centers and markedly masculine, the HIV/AIDS epidemic is currently characterized by heterosexualization, feminization, interiorization and pauperization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
185

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(267 citation statements)
references
References 6 publications
3
79
0
185
Order By: Relevance
“…Injectable drug use (IDU) is not an important via of exposure in the North and Northeast regions of Brazil, a fact confirmed by only 17 registered cases in the IDTNP. Other authors have reported a high rate of IDU in the Southeast region, supplanting heterosexual exposure 3,11 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Injectable drug use (IDU) is not an important via of exposure in the North and Northeast regions of Brazil, a fact confirmed by only 17 registered cases in the IDTNP. Other authors have reported a high rate of IDU in the Southeast region, supplanting heterosexual exposure 3,11 .…”
Section: Discussionmentioning
confidence: 94%
“…Of the 828 patients investigated, 254 died (30.7%) and of these, 194 (76.4%) died during the initial attendance and 44 (17.3%) within the first 48 h of hospitalization. The average number of admittances per patient was 1.5 ± 1.4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The number of infectious complications at death was of 2.1 ± 1.1 (0-8) and 231 (90.9%) patients presented up to three opportunistic infections at death.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,12,16 One study found a 4.1% annual increase in the incidence rate of male cases in the large cities of the Southeast macro-region between the years of 1990 and 1996; the corresponding figure for small southeastern municipalities was 20.8%. 16 Consequently, to appropriately design and implement adequate control measures, a better understanding of the characteristics of HIV infection in relatively small Brazilian communities and rural areas is urgently needed.…”
Section: Introductionmentioning
confidence: 99%